The Dynamics of Gender Differences on Tourism Governance in Indonesia - Nurhaeni, Ismi Dwi Astuti; Popping, Roel; Sugiarti, Rara; Nugroho, Rino Ardhian (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
Research on gender and tourism is very important at least because of three reasons. First, processes involved in tourism are constructed out of gender ideologies in the society. Second, gender relations contribute to the dynamics of the fluidity of gender identity in tourism. Finally, gender perspective is a tool for understanding the relationship between tourism and social process. Unfortunately, there have been limited studies on gender in tourism. This study offers empirical evidence of gender in tourism governance from Indonesia’s experience. It assesses the gender differences in tourism governance by proposing three variables, namely involvement, competence, and barriers to women and men involvement in tourism governance. The study was conducted in Karangayar regency in Indonesia, with the survey method as a data collection technique. No less than four hundred respondents were recruited in the survey, comprising of two hundred men and two hundred women. Mokken scale analysis was employed to analyze the collected data. Using the gendered perspective framework, the findings show three results. First, there is significant difference in the involvement of men and women in Indonesia’s tourism governance. Secondly, there is no significant difference between the competence of women and men in tourism governance. Lastly, it is found that there is no significant difference between the barriers of women and men in tourism governance. Therefore, while gender ideology still occurs in tourism governance, it has increasingly reduced.